Identification of an indole biodegradation gene cluster from Providencia rettgeri and its contribution in selectively biosynthesizing Tyrian purple - Li, Feifei; Deng, Huaxiang; Zhong, Biming; Ruan, Banlai; Zhao, Xixi; Luo, Xiaozhou (Frontiers in Bioengineering and Biotechnology, 2023)
Tyrian purple, mainly composed of 6, 6'-dibromoindigo, is a precious dye extracted from sea snails. In this study, we found Tyrian purple can be selectively produced by a bacterial strain GS-2 when fed with 6-bromo-tryptophan in the presence of tryptophan. This GS-2 strain was then identified as Providencia rettgeri based on bacteria genome sequencing analysis. An indole degradation gene cluster for indole metabolism was identified from this GS-2 strain. Heterologous expression of the indole degradation gene cluster in Escherichia coli BL21(DE3) and in vitro enzymatic reaction demonstrated that the indole biodegradation gene cluster may contribute to selectively biosynthesizing Tyrian purple. To further explore the underlying mechanism of the selectivity, we explored the intermediates in this indole biodegradation pathway using liquid chromatography electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF-MS/MS), which indicated that the indole biodegradation pathway in Providencia rettgeri is the catechol pathway. Interestingly, the monooxygenase GS-C co-expressed with its corresponding reductase GS-D in the cluster has better activity for the biosynthesis of Tyrian purple comparing with the previous reported monooxygenase from Methylophaga aminisulfidivorans (MaFMO) or Streptomyces cattleya cytochrome P450 enzyme (CYP102G4). This is the first study to show the existence of an indole biodegradation pathway in Providencia rettgeri, and the indole biodegradation gene cluster can contribute to the selective production of Tyrian purple.